ANALISIS KESESUAIAN ALAT TANGKAP DENGAN KEWILAYAHAN DALAM MENUNJANG PEMBANGUNAN PERIKANAN TANGKAP DI KABUPATEN BELITUNG - M. Nizar Dahlan; Budy Wiryawan; Bambang Murdiyanto; A. Fauzi; Mulyono S. Baskoro (Institut Pertanian Bogor, 2011)
There are 13 catching tools for fisheries that usually used in Belitung Regency, but those still need to be developed based on characteristic of each sub region in Belitung Regency. This research aim is to determinate the appropriation between all fisheries catch tools to each sub regions in Belitung Regency. This research is held in Sijuk, Tanjung Pandan, Badau, and Membalong Subregions in Belitung Regency. Analysis that used in this research are descriptive analysis, fish resource analysis, feasibility analysis for catch fisheries effort and Location Quotient (LQ) analysis. The result are there 13 fish catch tools usually used in Belitung Regency, and there are only seven fish catch tools that appropriate with each sub region, they are troll lines, large stationary fish trap and bubu that suitable if developed in Sijuk Sub-region, with each LQ value 2,49; 1,32; and 1,61; boat seine and drift gill net that suitable if developed in Tanjung Pandan Sub-region, with each LQ value 1,88 and 1,84; trammel net that suitable in developed in Badau Sub-region, with LQ value 2,83; and the last is boat fishing platform that suitable if developed in Membalong Sub-region, with LQ value 5,40. The conclusions are Sijuk could become basis for troll lines, large stationary fish trap and bubu; Tanjung Pandan could become basis for boat seine and drift gill net; Badau could become basis for trammel net; and Membalong could become basis for boat fishing platform.